Status of prerequisite and HACCP program implementation in Iowa and Kansas restaurants: Sanitarians’ perspective - Roberts, Kevin R.; Barrett, Betsy; Sneed, Jeannie (International Association for Food Protection, 2008)
The purpose of this study was to obtain baseline data about the presence of HACCP and prerequisite programs in chain and independent restaurants from the perspective of sanitarians who inspect restaurants and to determine how those programs have changed over the past five years. A three-part written questionnaire was distributed to all Iowa and Kansas sanitarians; 36 Iowa sanitarians (35%) and 18 Kansas sanitarians (41%) responded. The prerequisite program most often lacking in independent restaurants was a system of standardized recipes with critical control points (4%). Sanitarians noted little improvement in prerequisite programs over the past five years. Employee knowledge, time, and manager knowledge are identified as the top three barriers to implementing prerequisite and HACCP programs. Results indicate that important food safety practices need to be implemented in Iowa and Kansas restaurants. Sanitarians play an important role in improving food safety practices in restaurants and if more time were available to conduct inspections, sanitarians could provide referrals and resources specific to the needs of the operations to support food safety improvements.
Keywords: Food safety; HACCP